Sustainable minerals operations in the developing world - Marker, Brian (Geological Society special publication ;, 2005)
The sustainable development of minerals, which are non-renewable resources, is a major challenge in today's world. In this regard the true definition of 'sustainability' is a debating point itself: can such a concept exist with respect to non-renewable resources? This Special Publication gives examples from developing countries of all scales of mineral extraction. It reviews environmental, economic, health and social problems and highlights the need to solve these before sustainability can be achieved.